220k views
0 votes
Find the inverse of the following function g(x) = -2x+3

2 Answers

2 votes

Answer:


(y+3)/(2)

Explanation:

Find the inverse of the following function g(x) = -2x+3-example-1
User David Storey
by
4.8k points
3 votes

Answer:


g(x)^-1 = (-x)/(2) +(3)/(2)

Explanation:

1) swap x and y

x = -2y + 3

2) solve for y


x=-2y+3


2y=-x+3


y=(-x)/(2) + (3)/(2)

User JanOlMajti
by
6.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.